2021
DOI: 10.1111/prd.12365
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of the oral microbiome

Abstract: The composition of the oral microbiome has been reviewed previously. 5 Representatives of the Bacteria, Archaea, fungi, protozoa and viruses are present. Recent studies have revealed major new branches of the Bacteria and Archaea. The Candidate Phyla Radiation group within the domain Bacteria may make up to half of bacterial life on earth and members of this group appear to be ubiquitous. 6,7 Interestingly, the organisms within this group studied thus far are small in size, typically passing through filters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 115 publications
(184 reference statements)
3
78
1
Order By: Relevance
“…Given that some studies have identified networks of bacteria present in diseased states, it is possible that pathogenic bacteria are acting in consortia with other microorganisms to drive community-level shifts in the microbiome towards a diseased state. Due to the considerable overlap in the functional potential of bacterial species, some studies have suggested that a better understanding of disease etiology may be obtained by studying the functional activities of microbes, as opposed to attempting to identify a specific microbial composition related to disease [ 119 , 182 ]. Functional analyses are warranted in the future, using techniques in metabolomics, proteomics, metagenomics, and metatranscriptomics to study changes in functional profiles of the microbiome associated with EC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that some studies have identified networks of bacteria present in diseased states, it is possible that pathogenic bacteria are acting in consortia with other microorganisms to drive community-level shifts in the microbiome towards a diseased state. Due to the considerable overlap in the functional potential of bacterial species, some studies have suggested that a better understanding of disease etiology may be obtained by studying the functional activities of microbes, as opposed to attempting to identify a specific microbial composition related to disease [ 119 , 182 ]. Functional analyses are warranted in the future, using techniques in metabolomics, proteomics, metagenomics, and metatranscriptomics to study changes in functional profiles of the microbiome associated with EC.…”
Section: Discussionmentioning
confidence: 99%
“…Host genetics contribute in shaping the oral microbiome, but twin studies suggest environmental and lifestyle factors are the main drivers in shaping oral microbial communities [ 116 , 117 , 118 ]. Previous studies have examined the impact of various sociodemographic and lifestyle variables, including diet [ 119 ], geography [ 120 ], cohabitation [ 121 ], and race/ethnicity [ 120 , 122 ], but current evidence suggests these factors may only account for a small proportion of the inter-individual variation seen in the oral microbiome [ 103 ]. Perhaps one of the most important factors that modifies the oral microbiome is oral health [ 119 ].…”
Section: Oral Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…For example, alterations of the oral microbiota occur in individuals with diabetes. It has been suggested that an increase in blood glucose concentration in diabetic patients disrupts the homeostasis of the oral microbiota [ 28 ]. In obese patients, a significant decrease in microbial diversity has been observed in comparison with healthy individuals [ 29 ], while this difference was significantly less noticeable at the level of the gustatory papillae [ 5 ].…”
Section: Characteristics Of the Oral Microbiotamentioning
confidence: 99%
“…In xerostomia (dry mouth feeling) caused by Sjogren’s syndrome (altered salivary glands), an increase in infections caused by nonoral bacteria has been shown [ 30 ]. As saliva plays a key role in the maintenance of oral heath, a decreased salivary flow, and therefore reduced immune protection by saliva, likely explains this disorder [ 28 ].…”
Section: Characteristics Of the Oral Microbiotamentioning
confidence: 99%